ANALYSIS OF CONCEPT UNDERSTANDING OF 2ND SEMESTER MATHEMATICS COURSES - Nadiya Okta Rosansi (Teaching and General Education Studies, 2025)
This study aims to analyze the level of student concept understanding of Semester 2 Mathematics courses, identify the most difficult concepts to understand, and find forms of misconceptions and factors that influence them. The research used a qualitative descriptive approach with data collection techniques in the form of tests, in-depth interviews, classroom observations, and documentation. The research subjects were 2nd semester students of the Elementary School Teacher Education Study Program at PGRI Silampari University. The results showed that most students were in the moderate to low understanding category, with a tendency to memorize formulas without understanding their conceptual meaning. The most difficult materials to understand are function limits, mathematical logic, and linear function graphs. Common misconceptions include erroneous assumptions about the concept of limit and logical inference. Factors that influence understanding include initial ability, learning strategies, learning motivation, learning style, and learning environment. This study suggests the need for a learning approach that emphasizes conceptual understanding, the use of visual media, and the strengthening of contextual learning in order to create a more meaningful mathematics learning process.